Analisis Pengendalian Persediaan Bahan Baku Songkok ZNR dengan Menggunakan Metode Material Requirement Planning (MRP) - Muhammad Ahyat Daroini; Abdurrahman Faris Indriya Himawan (Universitas Muhammadiyah Gresik, 2021)
Background - This research is a case study research on the supply of raw material for ZNR skullcap which has advantages and disadvantages when product demand increases. Objective - The objectives of this study were to analyze how the implementation of raw material inventory control carried out by the company to determine the number of orders and the right time to place an order for raw materials so as to minimize the total costs incurred by the company by using the Material Requirement Planning (MRP) method. Design/Methodology/Approach - This research uses descriptive quantitative approach and MRP method with Lot Sizing, namely Lot for Lot (LFL), Part Period Balancing (PPB), and Wagner Whitin Algorithm (AWW). Findings - Using Lot Sizing PPB has the smallest inventory cost of Rp 229.820.- compared to LFL and AWW calculations. Research implications - In an effort to control raw material inventories related to costs, companies need to consider in terms of planning raw material requirements. Ensure the quantity to be produced in the next period based on the master production schedule so that the amount of raw material purchases can be ascertained so as not to experience overstock and raw material shortages. Research limitations – The PPB method will be difficult to use if the cost of storage is greater than the cost of ordering so it is difficult to determine the value of the Economic Part Period (EPP).